Making and unmaking public health in Africa : ethnographic and historical perspectives - Prince, Ruth Jane; Marsland, Rebecca (Cambridge Centre of African Studies series., 2014)
Africa has emerged as a prime arena of global health interventions that focus on particular diseases and health emergencies. These are framed increasingly in terms of international concerns about security, human rights, and humanitarian crisis. This presents a stark contrast to the 1960s and '70s, when many newly independent African governments pursued the vision of public health "for all," of comprehensive health care services directed by the state with support from foreign donors. These initiatives often failed, undermined by international politics, structural adjustment, and neoliberal.